Structural Design Optimization of Steel Beams and Frames with Web-Tapered Members Using the PSO-FEM Algorithm - Piotr Sych; Marek Słoński (Computer assisted methods in engineering and science, 2021)
This paper presents an algorithm for structural design optimization of steel beams and frames with web-tapered members using the particle swarm optimization (PSO) algorithm and the finite element method (FEM). The design optimization is done in accordance with Eurocode 3 (EC 3) for the minimum mass. The proposed algorithm is more flexible and efficient than traditional design methods based on a trial and error approach. The effectiveness of the presented PSO-FEM algorithm is evaluated on examples of the size optimization of web-tapered members cross-section. The results show that the PSO-FEM algorithm is feasible and effective for finding useful designs.